A companion to Francisco Suárez - Salas, Victor M.; Fastiggi, Robert L.; Coujou, Jean-Paul (Brill's companions to the Christian tradition ;, 2015)
A Companion to Francisco Suárez examines the rich philosophical and theological thought of one of the Society of Jesus' most celebrated luminaries of all time.